TINJAUAN LOCA (LETTER OF COORDINATION AGREEMENT) ANTARA UNIT ATS Reporting Office (ATS-RO) DENGAN LION AIR DALAM PROSES PENGAJUAN FLIGHT PLAN DI AIRNAV CABANG PONTIANAK - Rezki Iqbal Ramadyanto; Kusno; Putu Agus Valguna (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This final project explains what the author faces about assigning a flight information service to the Air Traffic Service Reporting (atsro) pontianak. Flight plan lion air at an airnav offshoot pontianak is often sent by lion air at a time convenient to the estimate of block time (eobt). The problem lies in the lack of knowledge of a lion air foo regarding the provision of a flight plan that causes the flight information service in an atsro pontianak unit. Thus, the writer has devised this scientific work to offer both input and advice to solve the present obstacles and to deliver aviation traffic services effectively and efficiently without forgetting the aspect of safety. The challenge can be solved by performing an advanced socialization to help foo airlines understand ordinances and rules in an application for a flight plan.